2013 IEEE 19th International Symposium on Asynchronous Circuits and Systems 2013
DOI: 10.1109/async.2013.9
|View full text |Cite
|
Sign up to set email alerts
|

Unfaithful Glitch Propagation in Existing Binary Circuit Models

Abstract: We show that no existing continuous-time, binary value-domain model for digital circuits is able to correctly capture glitch propagation. Prominent examples of such models are based on pure delay channels (P), inertial delay channels (I), or the elaborate PID channels proposed by Bellido-D\'iaz et al. We accomplish our goal by considering the solvability/non-solvability border of a simple problem called Short-Pulse Filtration (SPF), which is closely related to arbitration and synchronization. On one hand, we p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…Indeed, the result immediately follows from the fact that the adversary is free to always choose η n = 0, i.e., make the η-involution channels behave like involution channels. In [6], [5], it has been shown that no circuit with involution channels can solve bounded-time SPF, which completes the proof.…”
Section: Faithfulness Of Involution Channels With Adversarial Choicementioning
confidence: 57%
See 3 more Smart Citations
“…Indeed, the result immediately follows from the fact that the adversary is free to always choose η n = 0, i.e., make the η-involution channels behave like involution channels. In [6], [5], it has been shown that no circuit with involution channels can solve bounded-time SPF, which completes the proof.…”
Section: Faithfulness Of Involution Channels With Adversarial Choicementioning
confidence: 57%
“…The Lipschitz property is obtained exactly as in the proof of Lemma 7, by differentiating g(∆ 0 ) and using ∆ 0 < δ ↑ ∞ + η + . We summarize the consequences of the previous lemmas in the following theorem, which extends [5,Thm. 12] to the η-involution model: Theorem 9.…”
Section: Faithfulness Of Involution Channels With Adversarial Choicementioning
confidence: 84%
See 2 more Smart Citations
“…2: Principle functionality of a single-history delay model. Based on the input-to-previous output transition time T , the delay δ(T ) is determined [6].…”
Section: Introductionmentioning
confidence: 99%